Improving Madrasah Leadership: The Effectiveness of Integrated Training Models (Transformational, Technological, and Character) in the Digital Era - Rahmadani, Rahmadani; Aswad, Muhammad; Ummu Athiyah, Cut Nyanyak (Dinasti Review, 2026)
The leadership of madrasah heads is a key determinant in facing digital transformation and strengthening character education. This study aims to evaluate the effectiveness of madrasah head training programs and test the novelty of training models that integrate transformational leadership, educational technology, and Islamic character. Using a Research and Development (R&D) approach with a 4-D model, the research involved 30 madrasah heads within the Ministry of Religion of Banjarmasin City. Data were collected via Likert-scale questionnaires, observations, and interviews, and then analyzed using the Paired Sample T-Test. The results showed a significant increase in post-training competencies, with the highest score increase in the aspect of educational technology (73%), followed by character education (42%), and transformational leadership (41%). Additionally, 90% of participants successfully adopted the e-learning platform, and 85% actively participated in leadership simulations. This study concludes that the integrated training model is effective in enhancing the managerial competence and adaptability of madrasah heads, while also having a positive impact on teacher motivation and student discipline.